Vegetables consumed in Brazilian cuisine as sources of bioactive amines. (April 2021) - Dala-Paula, Bruno M.; Starling, Maria de Fátima V.; Gloria, M. Beatriz A.
Abstract: Polyamines contribute to longevity and a high dietary consumption of spermidine, or its supplementation, exerts cardioprotective effects and can increase lifespan. Bioactive amines have a significant effect on human health and disease. Ten bioactive amines were investigated in the edible parts of 12 different vegetables, typical of the Brazilian cuisine: broccoli, cauliflower, eggplant, jiló (scarlet eggplant), tomato, green onion, parsley, spinach, capers, cassava, heart of palm and bean sprouts. Free amines were extracted with 5% trichloroacetic acid, separated using ion-pair reverse phase HPLC and quantified fluorometrically after post-column derivatization with o -phthalaldehyde. The average total amines ranged from 0.47 to 4.51 mg/100 g, except for eggplant and bean sprouts, which were >10 mg/100 g. Spermidine was the most frequent amine in all the vegetables, followed by putrescine, agmatine and spermine. Histamine was found in eggplant, jiló, tomato (all from the Solanaceae family), spinach, parsley, capers and bean sprouts. Tyramine was also found in fruits of the Solanaceae family, green onion, spinach, parsley and heart of palm. Cadaverine was only found in bean sprouts. The neuroactive amines, serotonin, 2-phenylethylamine and tryptamine were found at trace concentrations in some vegetables. The skin and the core of eggplant had higher histamine than the pulp; therefore, distribution of amines depends on vegetable portion, which can be reduced for sensitive individuals to avoid histamine intoxication. Graphical abstract: Image 1 Highlights: Spermidine was found in all vegetables. Broccoli is a good source of spermidine. Eggplant, jiló, tomato, spinach and bean sprout are sources of histamine. Eggplant skin had the highest histamine and tyramine levels. Cadaverine was only found in bean sprout (Leguminosae).